Indium tin oxide thin films: an ideal transparent and conductive oxides contact for solar cells application - Aliyu, Kabiru Isiyaku; Ali, Ahmad Hadi; Nayan, Nafarizal (Penerbit UTHM, 2020)
Transparent and conducting oxides (TCOs) materials usually demonstrates simultaneously an exceptional properties such as high optical transmittance and good electrical conductivity[1]. TCOs materials have attracted a lot of interest, since after the first report of transparent and conductive cadmium oxide films in 1907 [2]. The increasing demands and advancement of optical and optoelectronic devices such as portable and flexible electronics, displays, solar cells, multi-functional windows and not long ago the transistors are some of the reasons for the huge interest [2,3]. Furthermore, the integration of different materials like metals, semiconductors, ceramics, plastics molecular and polymer organics into these devices have called for the provision of an improve TCO materials with required functional morphology, high performance and new processibility [5].